Designing Game-based Learning To Foster The Cross Cultural Cognition - Limantoro, Singgih Widodo; Datu, Yerly Arnold (Widya Mandala Catholic University Surabaya, 2019)
Boredom would be the biggest challenge in realizing a successful learning - effective and joyful learning. Boredom could happen in any learning when the students learn what they do not need or and they do not enjoy the conventional way of learning. In this case study, the writer would design game-based learning to foster the cross cultural cognition in Business Cross Cultural materials. By designing and playing games for learning BCC materials, the writer tried to create the effective and joyful learning. In this research, the writer would use fives phases of the research in designing the game-based learning. Moreover, the writer would investigate their joy and effectiveness of learning by using two different groups of totally 40 participants of Business English students that learn BCC - the experiment group that would use the game-based learning and the controlling group that had learnt without it. And the research results are there was insignificant difference in cognitive learning but the game-based learning could enhance the joy and motivation of learning.